Development and validity of an educational folder for pulmonary tuberculosis sputum collection - Karine Nascimento da Silva; Sabrina Alaide Amorim Alves; Maria do Socorro Vieira Lopes; Antonio Germane Alves Pinto; Maria Lúcia Duarte Pereira; Edilma Gomes Rocha Cavalcante (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to develop and validate an educational folder for pulmonary tuberculosis sputum collection. Method: a methodological study, developed in four phases: project design, bibliographic survey, development, and content and appearance validity. For validity, the Content Validity Index greater than or equal to 0.80, the Kappa Coefficient and the Suitability Assessment of Materials were adopted. Results: an educational folder was developed containing the recommended steps for quality sputum collection. It was validated by 19 expert judges in the first validity cycle, obtaining an overall Content Validity Index of 0.90, perfect agreement among judges, with a total Kappa of 0.83 and superior suitability. Conclusion: the material is valid, as it contains suitable, simple and attractive language, illustrations and layout, indicating perfect agreement and reliability. Thus, it has the potential to assist in carrying out the recommended steps for correct sputum collection and enable the correct diagnosis.